PENYISIHAN AMONIAK DALAM UPAYA MENINGKATKAN KUALITAS AIR BAKU PDAM-IPA BOJONG RENGED DENGAN PROSES BIOFILTRASI MENGGUNAKAN MEDIA PLASTIK TIPE SARANG TAWON - Widayat, Wahyu; suprihatin, Suprihatin; Herlambang, Arie (Jurnal Air Indonesia, 2010)
In big cities, the water quality of rivers used as the main raw water sources is getting worse and worse. That is caused by a lot of improper wastewater management systems, especially in industrial and settlement areas. As an example, the raw water of PDAM TKR Bojong Renged which is taken from Cisadane Rives contains Ammonia 3.8 mg/l and it means that the content is not allowed to be used as the raw water for drinking water purpose. To cope with the problem, a bofiltration process can be used as one alternative to reduce Ammonia till the required standard quality. A honeycomb tube type made plastic was the media of biofilter reactor. Operational condition was varied with HRT (Hydrolysis Retention Time) between 1-4 hours and air supply between 0-30 l/minute. The best process condition was found at 2 hour-HRT and 20 l/minute air supply and the Ammonia removal efficiency was about 65%. The linear regression equation was ya = -91.19xa + 77.12, where Y is for removal efficiency and the axis X is for Ammonia loading. Keywords: raw water quality, ammonia, biofiltration, honeycomb tube, removal efficiency,